2021
DOI: 10.1002/bdd.2276
|View full text |Cite
|
Sign up to set email alerts
|

Blood retinal barrier and ocular pharmacokinetics: Considerations for the development of oncology drugs

Abstract: Tyrosine kinase inhibitors (TKIs) are an example of targeted drug therapy to treat cancer while minimizing damage to healthy tissue. In contrast to traditional oncology drugs, the toxicity profile of targeted therapies is less well understood and can include severe ocular adverse events, which are among the most common toxicity reported by these therapeutics. Inhibition of Mer receptor tyrosine kinase (MERTK) promotes innate tumor immunity by decreasing M2‐macrophage polarization and efferocytosis. This mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…On one hand, transporter-mediated DDIs at the BRB due to concomitant treatment with drugs which inhibit ABCB1 and/or ABCB2 could contribute to enhanced ocular and in particular retinal toxicity of drugs that normally penetrate poorly into the eye, such as imatinib ( Ho et al, 2013 ), other tyrosine kinase inhibitors ( Williamson and Reddy, 2021 ), ciprofloxacin ( Ramirez et al, 2011 ), tamoxifen ( Griffin and Garnick, 1981 ; Noureddin et al, 1999 ; Grzybowski et al, 2015 ) and methotrexate ( Balachandran et al, 2002 ; Iqbal et al, 2005 ; Sbeity et al, 2006 ; Sharma and Sharma, 2011 ; Grzybowski et al, 2015 ) (see Supplementary Table S3 ). On the other hand, DDIs could generate therapeutic benefits by enhancing the ocular penetration of systemic treatments for retinal disorders struggling to cross the BRB, which represents so far a major challenge for ocular drug delivery ( Jordán and Ruíz-Moreno, 2013 ; Agrahari et al, 2016 ; Pascual-Pasto et al, 2017 ; Kim and Woo, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, transporter-mediated DDIs at the BRB due to concomitant treatment with drugs which inhibit ABCB1 and/or ABCB2 could contribute to enhanced ocular and in particular retinal toxicity of drugs that normally penetrate poorly into the eye, such as imatinib ( Ho et al, 2013 ), other tyrosine kinase inhibitors ( Williamson and Reddy, 2021 ), ciprofloxacin ( Ramirez et al, 2011 ), tamoxifen ( Griffin and Garnick, 1981 ; Noureddin et al, 1999 ; Grzybowski et al, 2015 ) and methotrexate ( Balachandran et al, 2002 ; Iqbal et al, 2005 ; Sbeity et al, 2006 ; Sharma and Sharma, 2011 ; Grzybowski et al, 2015 ) (see Supplementary Table S3 ). On the other hand, DDIs could generate therapeutic benefits by enhancing the ocular penetration of systemic treatments for retinal disorders struggling to cross the BRB, which represents so far a major challenge for ocular drug delivery ( Jordán and Ruíz-Moreno, 2013 ; Agrahari et al, 2016 ; Pascual-Pasto et al, 2017 ; Kim and Woo, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, understanding the relationship between efflux ratio and ocular exposure is crucial for PK understanding. As previously discussed (Williamson and Pilla Reddy 2021 ), melanin binding must be considered to accurately assess the free ocular exposure. However, differences in melanin levels across species and the localization of melanin within ocular tissues including the RPE layer (Jakubiak et al 2018 ; Leblanc et al 1998 ) hinders the interpretation of the free levels.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that another potential application of PEGylation could be to modulate ocular biodistribution of systemically administered proteins or antibodies. We sought to investigate if PEGylation could impact the biodistribution of a full length antibody targeting MerTK, a therapeutic target of interest with risk of ocular toxicity …”
Section: Introductionmentioning
confidence: 99%
“…MerTK, a member of the Tyro3-Axl-Mer receptor tyrosine kinase family, plays an important role in tissue homeostasis, remodeling, preventing autoimmunity, and controlling inflammation. , MerTK recognizes externalized phosphatidylserine on apoptotic cells via the bridging molecules Gas6 or ProteinS, , and engulfs apoptotic cells in a process known as efferocytosis. , MerTK expressed on tumor associated macrophages (TAMs) is hypothesized to promote an immune suppressive tumor microenvironment, therefore inhibiting antitumor immunity . Several groups have published studies investigating antagonism of MerTK to promote antitumor immune response, showing promising results as a single agent as well as in combination with checkpoint immune therapy , and cytotoxic agents. While MerTK is a target of interest for cancer immunotherapy, on-target ocular toxicity remains a key concern for clinical development . MerTK is expressed on retinal pigment epithelial cells (RPEs) and has an essential role in the diurnal phagocytosis of shed photoreceptor outer segments. , Mutation or knockout of MerTK in mice results in accumulation of cell debris and photoreceptor death leading to loss of vision. , Consistent with genetic studies, therapeutic blockade of MerTK has been shown to induce retinal degeneration in preclinical models with both a small molecule and an antibody …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation